ADSORPTION OF HEAVY METALS Pb, Cd, Hg, Ag, Fe, AND Zn FROM SOLUTION BY RICE STRAW - Soediatmoko Soediman (Purifikasi, 2011)
As rice straw is abundantly available in Indonesia and other tropical developing countries as an agricultural waste, this material may be used as a simple and environmentally friendly way to remove heavy metals from contaminated water sources for human use. In this paper, untreated rice straw was studied towards its ability to adsorb several heavy metals Pb, Cd, Hg, Ag, Fe, and Zn ions from aqueous solutions at concentrations of 2 ppm and 20 ppm, in individual and mixed solutions. In individual solutions at 2 ppm, the order of metal sorption by straw when calculated on a weight basis is Zn > Pb > Cd > Ag > Fe > Hg, at 20 ppm it is Pb > Fe > Cd > Zn > Hg > Ag. The selective order of the metal sorption at 2 ppm is: Cd > Zn > Pb > Ag > Fe ≈ Hg; while at 20 ppm, the order is Pb > Fe > Ag > Hg > Cd > Zn. Interestingly, in mixed solution experiments competitions between metals were occurred. The adsorption of the metals was also in line with the decrease of pH of the solutions, especially for Hg, suggesting that chemical reactions i.e. the release of H+ was occurred. Further studies on the potentials of rice straw to filter out heavy metals from contaminated water are warranted.